Dictionnaire historique: Trois siècles de mots de portugais du BrÉsil - Murakawa, Clotilde de Almeida Azevedo [UNESP] (My University, 2012)
The aim of this article is to present the methodology and the lexicological implementation of the Historical Dictionary of Brazilian Portuguese of the 16th to 18th centuries (DHPB), a research project carried out in the context of the Millenium Institutes Program of the Brazilian National Council for Scientific and Technological Development (CNPq - Brazil). The first stage was to gather together a set of highly detailed documents written over the three centuries of the colonial period from all over Brazil and to consign them to a database. The first founding text is the Letter of Pero Vaz de Caminha, going back to 1500, and the most recent dating to 1808, with the arrival of the Portuguese royal family in Brazil, fleeing the Napoleonic invasion. This database was used to organise a nomenclature of around 10,000 entries, covering the lexical repertoire of Brazilian Portuguese and including the following lexical information: gramatical category, written, spoken and morphological variants, the definitions of the various usages, with an attestation, figurative meanings, phraseology and the dating of the earliest attestation recorded in the documentation. A computer program was made to cater for all this information, using the Philologic software, which facilitates the writing of the dictionary articles. The DHPB can be considered a historical dictionary facilitating the systematic observation of how Brazilian Portuguese has developed.
Historical dictionary: Three centuries of words in Brazilian Portuguese
Keywords: Brazilian; Historical dictionary of Brazliian Portuguese; Lexical repertoire